Cyrsoid aneurysm of the cystic artery - Pereyra Bonasso, Jorge; Capandeguy, Enrique; Caritat, Ricardo; Zagia, Miguel; Delgado, Bolívar (Cirugía del Uruguay, 2020)
This communication refers to the case, which is perhaps unique in literature, of a cirsoid aneurism of the left branch of the cystic · artery. Clinically it is believed to be the probable cause of the hepatic colics presented by the patient. Radiologically it appeared in the cholecystogram fixed repletion defect of the gall bladder, !acunar un aspect. It was treated by a complete resection involving a cholecystectomy. The infrequent but varied pathology of the cystic artery is analized. The paper includes a discussion of presumptive diagnosis and the conduct to be applied when cholecystographic studies show repletion defects of the gall bladder.